Sikap Menyayangi Sesama Manusia dalam Perspektif Islam: Studi Takhrij dan Syarah hadis - Muhammad Rofi Fawwaz Mumtaz; Hidayatul Fikra; Dadah (UIN Sunan Gunung Djati Bandung, 2022)
This research aims to discuss imam Bukhari hadith No. 7376 on the virtues of loving fellow human beings, which is something that everyone needs to have for the sake of a good life. This research applies qualitative methods through literature studies with takhrij hadith and sharah hadith. The result of this study is the known quality of the hadith which is considered shahih because it meets the requirements of a hadith can be said to be shahih. From the sharah of hadith it is known that this hadith affirms to love each other, both in the form of loving, giving, respecting, appreciating and even forgiving mistakes. This research concludes that Islam has clearly explained through the Qur'anic verses, one of which is reinforced by this hadith, and the example that has been exemplified by the Prophet is an obligation as a human being that must be carried out. This study recommends continued research review of hadith on the attitude of love and respect to others of different beliefs or races and ethnicities so that it can be implemented in the lives of readers.